A new enzyme-linked immunosorbent assay for serological diagnosis of seal parapoxvirus infection in marine mammals - Badr, Yassien; Rahman, Md. Matiur; Ohno, Yoshito; Ishijima, Keita; Maeda, Ken; Kohyama, Kaoru; Kamatari, Yuji O.; Shimizu, Kaori; Okada, Ayaka; Inoshima, Yasuo (Journal of veterinary research, 2022)
Seal parapoxvirus (SPPV) infection has been reported among pinnipeds in aquaria in Japan; however, its seroprevalence is unknown. Therefore, an enzyme-linked immunosorbent assay (ELISA) was developed for serological diagnosis of SPPV infection. The gene encoding the major envelope protein of SPPV was cloned into the eukaryotic expression vector pAcGFP1-N1, which encodes the green fluorescence protein (GFP), thereby producing a fusion protein (Env-GFP). Parental and cloned vector DNA was independently transfected into cultured seal cells for the expression of GFP and Env-GFP. The wells of an ELISA plate were coated with either GFP- or Env-GFP-transfected cell lysates. The light absorbance of each serum sample was adjusted by subtracting the absorbance of GFP-coated wells from that of Env-GFP-coated wells. Sera from two spotted seals ( ), six beluga whales ( ), three Pacific white-sided dolphins ( ), and ten bottlenose dolphins ( ) from an aquarium in Japan were examined using the ELISA. Positive reactions were not observed, except in one preserved sample collected ten years ago from a naturally SPPV-infected spotted seal. The established ELISA could be useful in screening marine mammal sera for anti-SPPV antibodies.